Comfortable Room Condition for Working and Resting - Jovina Evangeline Wardana; Ova Candra Dewi; Joice Sandra Sari (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
This paper aims to determine the comfortable room condition in terms of room organization, lighting and room temperature. Due to the pandemic, many workers are forced to bring their outside home activities back home. Many of them struggle in finding one suitable and comfortable space as they do not have a dedicated space to do the work from home. A bedroom, as one of the potential rooms to maintain the balance between work and rest at home, are observed for space adjustment, especially the organisation of space, lighting and room temperature to maintain the comfort. The comfortable room condition needs to support the bedroom as a working and relaxing space. This study consists of literature review about space, lighting and temperature and observation of two study case studies. This study concludes that the room organization, lighting and room temperature affects the user physically and psychologically which results in the comfort of the user. As a worker, to increase comfort level and have good rest balance, the user needs to adjust the variables of lighting, room temperature and room organization to achieve the optimum comfort level.